Chronic Thromboembolic Pulmonary Hypertension: Take care to a“favourable” apparently evolution. A case report - Serra, W.; Oliviero, D.; Chetta et al., A. (Acta Biomedica Atenei Parmensis, 2011)
Chronic thromboembolic pulmonary hypertension (CTEPH) caused by intraluminal thrombus organization and fibrous stenosis or complete obliteration of pulmonary arteries, is a not rare but life-threatening complication of acute pulmonary embolism. The prognosis of medically treated patients with CTEPH is poor and worsens as pulmonary hypertension exacerbates. We describe the case of a 43-years old with a history of progressive shortness of  breath, hemoptysis, chest discomfort and syncope. Echocardiographic and imaging studies showed changes consistent with chronic thromboembolic pulmonary hypertension. Further work-up showed only moderate increase of  homocysteine level with negative features for lupus and others primary thrombophilic disease. The patient was managed adequately with thrombolytic and inotropic therapy; oral anticoagulation was started with improvement of his clinical status and was screened for pulmonary  thrombo endarterectomy, but he refused. The case presented despite its evolution ‘temporarily’ positive perhaps related to the reduction of hemodynamic overload through bronchial arteries, reiterates the importance of early surgical intervention, before it establishes the hypertensive vasculopathy. Abnormal pulmonary function at rest and after exercise stress test associated to non invasive echocardiographic measurements  are an excellent tool to identify the bad prognosis patients in CTEPH. We discuss the pathophysiology and conclude that in selected cases, pulmonary thromboendarterectomy is the best therapy,but only if executed early.